2019
DOI: 10.1371/journal.ppat.1007601
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-based small molecule repositioning reveals clinically approved urea-based kinase inhibitors as broadly active antivirals

Abstract: Influenza viruses (IVs) tend to rapidly develop resistance to virus-directed vaccines and common antivirals targeting pathogen determinants, but novel host-directed approaches might preclude resistance development. To identify the most promising cellular targets for a host-directed approach against influenza, we performed a comparative small interfering RNA (siRNA) loss-of-function screen of IV replication in A549 cells. Analysis of four different IV strains including a highly pathogenic avian H5N1 strain, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…Kinase inhibitors are high-yield targets, with new small molecule kinase inhibitors being developed every year and over two dozen small molecule kinase inhibitors already approved for human use 97 . Their potential as antiviral treatments has also been explored in recent years 91 , 98 100 . Viruses depend on host cell protein kinases for every step of their life cycle, including viral entry into the cell, cell cycle processes and cellular stress response 101 .…”
Section: Discussionmentioning
confidence: 99%
“…Kinase inhibitors are high-yield targets, with new small molecule kinase inhibitors being developed every year and over two dozen small molecule kinase inhibitors already approved for human use 97 . Their potential as antiviral treatments has also been explored in recent years 91 , 98 100 . Viruses depend on host cell protein kinases for every step of their life cycle, including viral entry into the cell, cell cycle processes and cellular stress response 101 .…”
Section: Discussionmentioning
confidence: 99%
“…All of these drugs were identified based on an understanding of the molecular mechanism of ALI. Although a few studies have been performed based on a group of genes, their results were not confirmed by well-designed experiments [10][11][12]. Thus, a genomic approach to identify drugs for potential repurposing is worth exploring, and in this work, we propose a highly efficient, genome-wide method to identify drugs to be repurposed for the treatment of ALI induced by H5N1 influenza virus infection.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, Lesch et al identified available compounds for a similar proportion of the hits from their influenza virus siRNA screen (43 compounds covering 14 of the total 133 hit genes). 38 We might have been able to identify more targets using this combination screening approach if more compounds covering more primary siRNA hits had been available. Therefore, the success of this combination screening approach highly depends on the availability of small-molecule compounds.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach has recently been reported in the search for host targets against influenza virus infection, whereby experimental or clinically approved drugs were selected based on the hits from an siRNA screen, enabling the identification of a host signaling pathway for targeting influenza virus. 38 Based on this hypothesis, we searched within the AstraZeneca compound collection for compounds that are annotated to be pharmacological regulators of the 1128 target genes. Only 122 targets had available compounds in the AstraZeneca compound collection.…”
Section: Discussionmentioning
confidence: 99%